A percepção do belo e a proporção divina - Marília Gerhardt de Oliveira (2007)
The aesthetic knowledge concerning the face one is widely important for the professionals of the Dentistry area and, moreover, it is of interest of the people of a general form. It has a trend, while professional, of if imposing the aesthetic values when really can be to observe the values of the proper individual. Many are the studies that present, of clear form, the differences between the individuals, as patient or people independent, how to its preferences, if compared with the ideas of beauty of the professionals of different areas. Being thus, objective in this chapter to integrate the reader to the presentation of the aesthetic one, not only in the scientific aspect, as measurable and quantitative object, as also in the artistic and social aspect. How to the beauty, the perception that if has of the things in day-by-day is basically utilitarian and conceptual. It has a bigger trend in if to perceive the things by means of the concepts proceeding from the language of the one that really eat is capable to sensitize our directions. However, it fits to remember that the language classifies and appraises the feelings, but is extremely impotent to describe them. It must always be had in mind that is in the sensible one - and not in the conceptual one, in the intellectual - that inhabits the being of the aesthetic object.